Distress and its Correlation with Potential Factors among Patients with Cancer in Vietnam - Dung Le; Huong Thi Mai Phan (Journal for Social Action in Counseling and Psychology)
A cancer diagnosis and treatment are stressful for patients. Evidence has shown that the prevalence of mental health problems among cancer patients is very high globally. To our knowledge, there are no studies related to cancer diagnosis and treatment in Vietnam, where the rate of death caused by cancer is at the 50th in the world. This study investigates the prevalence of distress and its correlations with potential factors among Vietnamese cancer patients. This is a cross-sectional study using a self-report questionnaire for cancer patients focused on examining socio-demographic characteristics, satisfaction with current marital status, current job, life in general, cancer-related distress, diagnosis, cancer stage, acceptance of illness, treatment methods, and perceived social support. The prevalence of distress among cancer patients was very high (91.7%). There were significantly higher distress scores in patients living in rural areas and not receiving chemotherapy and radiotherapy. Patients with higher satisfaction with their current employment status or satisfaction with life were less likely to have psychological distress. The patients’ belief in treatment methods and cancer also reduced the risk of experiencing distress. Rural Vietnamese cancer patients impacted by social determinants of health along with cancer-related factors might be experiencing higher psychological distress.